Study of quality indicators of fermented-milk cheese obtained from skimmed milk at a controlled content of calcium - Grynchenko, Nataliya; Tyutyukova, Daria; Pyvovarov, Pavlo (Eastern-European Journal of Enterprise Technologies, 2017)
The results obtained in the study of influence of calcium content in skimmed milk on organoleptic, physical, physical-chemical and technological properties were summarized. A method for regulating calcium content in milk using a natural ion exchanger, sodium alginate, was proposed. It has been shown that the use of natural sequestrants allows producers to reduce calcium content in milk to 50 %. In the framework of the conducted studies, a correlation between the degree of milk decalcification and the physical and chemical properties of the fermented clot and whey has been established. It was shown that removal of calcium from milk results in the destruction of caseinate-calcium-phosphate complex with a simultaneous decomposition of the casein micelles to submicelles. The found effect manifests itself by formation of a characteristic fermented clot and an increase in the weight fraction of soluble protein in whey. The influence of calcium content in milk on qualitative parameters of fermented-milk cheese, its microstructure and dispersion of protein particles was established. The boundary conditions of decalcification of milk were substantiated which allows producers to obtain fermented-milk cheese with high qualitative indicators. It was proved that decalcification of milk in a rational interval and at specified parameters enables production of fermented-milk cheese which is characterized by a spreadable consistency, absence of crumbs and whey separation. The organoleptic properties of fermented-milk cheese completely correlate with the indicator of moisture retaining ability which regularly grows with an increase in decalcification within a rational interval. Dispersion of fermented-milk cheese and the size of protein particles were established. A direct relationship between the size of protein particles and sedimentation stability of systems was revealed. An increase in colloidal stability was observed at a reduced calcium content resulting in a growth of the fraction of particles with a smaller diameter. The results obtained in the study completely reflect the theory of decomposition of casein micelles at a reduced calcium content in milk